Defining Locality in Genetic Programming to Predict Performance - GALVAN-LOPEZ, EDGAR (IEEE Press, 2010)
A key indicator of problem difficulty in evolutionary computation problems is the landscape?s locality, that is whether the genotype-phenotype mapping preserves neighbourhood. In genetic programming the genotype and phenotype are not distinct, but the locality of the genotypefitness mapping is of interest. In this paper we extend the original standard quantitative definition of locality to cover the genotype-fitness case, considering three possible definitions. By relating the values given by these definitions with the results of evolutionary runs, we investigate which definition is the most useful as a predictor of performance.
Proceedings of the 12th Annual Congress on Evolutionary Computation
CEC 2010: 12th Annual Congress on Evolutionary Computation
PUBLISHED
Barcelona, Spain
Keywords: Applied mathematics; genotype-phenotype; Genes & Society